Musik Kematian dalam Budaya Masyarakat Batak Karo : Sebuah Kajian Musikologis Interkultural - Bijak Ginting (Universitas Quality, 2017)
This report is based on field study which is conducted at the field study which is conducted at the end of every semester starting in 2001 unto July 2002. The research was conducted in Kabanjahe and Berastagi. It is a qualitative study of Batak Karo music culture based on various branches of science.Batak Karo funeral music is traditional music which has been existed for long time and has become a part of Batak Karo life. It is supposed that Batak Karo funeral music is a cultural heritage of Indian. This can be proved from the existence of Sembiring Brahmana clan, cremation and belief in God which is represented in there forms.The music instruments which are used in the funeral ritual processions are also used in the seculer music performances. The five Batak Karo music instruments are caloled Gendang Lima Sidalanen and the players are called Penggual. The funeral procession music uses short melody which is reported continuously until the singing and dancing (Landek) for the death is finished. The pitch has not been stated clearly but empirically it can be said that used two pentatonic pitches, namely; hemitonic and unhemitonic pitches.Up to now, having changed the instruments several times, Gendang Lima Sedalanen is still used. The changing of the music instruments and the duration of the funeral ritual procession music performance is caused by the sensitivy of Batak Karo musicans / artist to the beauty and the religious factors followed by Batak Karo societies.